Income taxes, property values and migration - Amihai Glazer; Vesa Kanniainen; Panu Poutvaara (Institute for the Study of Labor (IZA), 2005)
We consider taxation by a utilitarian government in the presence of heterogeneous locations within a country. We show that a utilitarian government never equalizes after-tax incomes, even when it can impose group-specific lump-sum taxes. If migration is impossible, a utilitarian government may even transfer income from the poor to the rich, reducing the rents earned by absentee landlords. The redistributive tax on the rich may be higher or lower when the rich can migrate than when they cannot.
Keywords: H21; H7; R21; R23; 330; taxes; land rents; property values; migration; redistribution; Einkommensteuer; Steuerwettbewerb; Bodenrente; Bodenpreis; Binnenwanderung; Einkommensumverteilung; Stadtökonomik; Theorie